Boom towns : restoring the urban American dream - Walters, Stephen John Kasabuski, 1953- (Stanford Economics and Finance, 2014)
American cities, once economic and social launch pads for their residents, are all too often plagued by poverty and decay. One need only to look at the ruins of Detroit to see how far some once-great cities have fallen, or at Boston and San Francisco for evidence that such decline is reversible. In Boom Towns, Stephen J.K. Walters diagnoses the root causes of urban decline in order to prescribe remedies that will enable cities to thrive once again. Arguing that commonplace explanations for urban decay misunderstand the nature our towns, Walters reconceives of cities as dense accumulations of ca.